Volume 1: Advances in Aerospace Technology; Energy Water Nexus; Globalization of Engineering; Posters 2011
DOI: 10.1115/imece2011-63157
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Wind on Air-Cooled Condenser Performance

Abstract: This paper documents the results of a field tests to determine the effect of wind on the performance of air-cooled condensers (ACCs) at power plants. Continuous measurements of wind speed, wind direction, cell inlet temperature and air flow and plant operating variables were made for several days at the El Dorado Energy Center. ACC performance was shown to be affected both by hot air recirculation and by fan performance degradation. Average recirculation, defined as the difference between the average cell inle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…These structural effects are also valid for a smaller scale objects, such as industrial fans. It is confirmed experimentally 19,20 that flow distortions due to crosswinds lead to increase in levels of structural vibrations of fan blades. It was found, in particular, that both acoustic and vibration structural responses of blades due to crosswind are similar and contain multiple superharmonics of the rotation frequency as well as first eigenfrequency of the blade.…”
mentioning
confidence: 70%
See 2 more Smart Citations
“…These structural effects are also valid for a smaller scale objects, such as industrial fans. It is confirmed experimentally 19,20 that flow distortions due to crosswinds lead to increase in levels of structural vibrations of fan blades. It was found, in particular, that both acoustic and vibration structural responses of blades due to crosswind are similar and contain multiple superharmonics of the rotation frequency as well as first eigenfrequency of the blade.…”
mentioning
confidence: 70%
“…11 Instruments for measurement of the local flow velocities, such as hot wires, hot films, and laser Doppler anemometers, are also widely used. 11,12,[19][20][21][22][25][26][27][28] In contrast to the computationally complex methods of the CFD involved into numerical studies of the flow separation, experimental detection and diagnostics of the flow separation are predominantly based on simple signal processing techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Duan Huishen et al [4][5] and Owen et al [6] studied the formation mechanism of hot air reflow and found through numerical simulation that the higher the wind speed, the more severe the hot air reflow. However, Maulbetsch and DiFilippo [7] found through field tests that at moderate wind speeds (3m/s to 7m/s), hot air reflow was the most serious, and wind inlet air temperature rises most. At higher wind speeds, There is a tendency for the hot air reflow to slow down and slow down.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that flow detachment at the periphery of the ACC banks is caused by cross-flow under the platform, which is induced by the center fans' intake and natural ambient winds [8][9][10][11][12][13][14][15][16]. This reduces volumetric effectiveness of the cooling fans of down to 70% at the ACC perimeter [6,15,[17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%